The very hungry caterpillar ebook - Carle, Eric (2016)
THE ICONIC #1 BESTSELLER • The all-time classic picture book starring the world’s favorite caterpillar! This Read & Listen edition features optional audio narration for compatible ebook readers. “Gorgeously illustrated, brilliantly innovative.”— The New York Times Book Review In the light of the moon a little egg lay on a leaf. One Sunday morning the warm sun came up and—pop!—out of the egg came a tiny and very hungry caterpillar. So begins the journey of Eric Carle’s most beloved storybook character. Follow along as one of nature’s loveliest marvels eats his way through an amazing variety of foods as he prepares to transform into a beautiful butterfly! An innovative, entertaining story that teaches little ones about counting and the days of the week, this book doubles as the perfect way to introduce change as a positive and necessary part of life.